The Effectiveness of the Scratch-Assisted Jigsaw Learning Model to Improve Students' Creative Thinking Skills and Science Literacy on the Topic of Measurement - Riki Perdana; Syifa Alifa; Sukardiyono Sukardiyono; Jumadi Jumadi (Postgraduate, University of Mataram, 2025)
This research developed and validated a Scratch-assisted Jigsaw learning instrument for teaching physics measurement concepts. It also investigated the model's impact on students' creative thinking skills and scientific literacy. A True Experimental Research design with a quantitative approach, using a pre-test post-test control group, was employed. The instrument underwent rigorous validation, including feasibility assessments and field tests. Effect size analysis determined the model’s impact. The developed instruments met eligibility standards and significantly enhanced students' creative thinking and scientific literacy. Hypothesis testing showed a significance value below 0.05. Effect sizes for creative thinking (0.33) and scientific literacy (0.32) were both medium, indicating a noticeable positive impact. The Scratch-assisted Jigsaw model is a reliable and effective approach, offering a valuable and innovative alternative for improving physics education quality by enhancing creative thinking and scientific literacy.